The Vertical Sterilizer (Boiling) Works at the PTPN IV Dolok Ilir Unit - Butar, Tua Naumarga Butar; Naibaho, Winfrontstein (Universitas Pahlawan Tuanku Tambusai, 2026)
Palm oil is a key product with a significant market share, crucial for the Indonesian economy. Indonesia is currently the world's largest CPO producer. Crude palm oil (CPO) and palm kernel oil (PK) offer numerous benefits. Ptpn Iv Dolok Sinumbah. Palm oil is one of the main products that has a market share, this is very important for the Indonesian economy. Indonesia is currently the largest CPO producer in the world. The benefits of crude palm oil (CPO) and palm kernel oil (PK) are numerous. CPO is widely used as industrial raw materials such as butter, soap, cosmetics, textiles, biodiesel and others. The data obtained from observations during the practical work are: The capacity of PKS PTPN IV DOLOK SINUMBAH is 30 tons / hour and processes Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO) and Palm Kernel. In the practical work that we have studied, especially at the thresher station 2 hoist cranes are used in each processing, each with a capacity of 5 tons. The thresher rpm speed from the data we obtained is at rpm 22-23 rpm, so that the loose fruit can be separated from the bunch.